Standardised Uptake Value in Organ Confined Prostate Cancer in 68-Ga- Prostate-Specific Membrane Antigen Positron Emission Tomography-Computed Tomography Scan and its Correlation with Prostate Specific Antigen Level and Gleason Score - Ali, Haider; Rashid-ul-Amin, Syed; Hai, Abdul (Journal of cancer & allied specialties, 2023)
A positron emission tomography (PET) scan and a computed tomography (CT) scan are an integral part of oncological imaging and other modalities such as magnetic resonance imaging, CT or bone scintigraphy have some limitations in staging the workup of prostate carcinoma. Combined with tissue-specific markers like prostate-specific membrane antigen (PSMA), positron emitter-based functional imaging results have improved. Our study aimed to determine the Standardised Uptake Value (SUVmax) in prostate adenocarcinoma that is confined to the organ in Ga-68-PSMA PET-CT scans and how it correlates with prostate-specific antigen (PSA) levels and Gleason score (GS). This cross-sectional study was conducted at Sindh Institute of Urology and Transplantation (SIUT), Karachi, and includes subjects referred for a Ga68-PSMA PET-CT scan from September 2017 to January 2022. Histopathologic-proven adenocarcinoma prostate patients with organ-confined disease and PSA levels obtained within 6 weeks before the PSMA-PET-CT scan were included in the study. PET-CT images were semi-quantitatively analysed by measuring SUVmax and the result was interpreted using statistical software SPSS version 22.0. A total of 154 patients were analysed. The mean age of patients was 66.57 ± 8.86 years. The GS of all patients ranges from 6 to 10. The mean and median PSA levels were 32.33 ng/mL (range: 0.004-306.00) and 14.20 ng/mL, respectively. The mean SUVmax of all prostatic lesions was 14.67 ± 12.58 and the median value was 10.76. SUVmax was higher in patients with a PSA level of more than ten than those with a <10. The correlation of SUVmax with PSA and GS showed a significant correlation. The SUVmax of organ-confined prostate cancer correlates well with PSA level and GS Median SUVmax and PSA directly relate to GS.